Membaca Pemikiran Bediuzzaman Said Nursi tentang Signifikansi Agama dan Identitas Bagi Kemajuan Sosial - Hamsah, Ustadi (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
Identity is the basic principle of the society. The search for identity and effort to build and defend identity is the fundamental struggle for society. Theoretically, the prosperous society depends on the strength of its identity. The society can achieve the social advancement, extraordinary ethos, and creativity because of their strong identity. This article attempts to explain how identity and self-capability contribute to the social advancement. This explanation refers to the thought of the modern gigantic Turkish thinker, Bediuzzaman Said Nursi. Exploring the construction of Said Nursi?s concept of Islamic identity and self-capability in developing society, especially in social prosperity and economic progression, this paper attempts to explain the foundation of social and individual prosperity. According to Said Nursi, the development of culture and civilization will be established by powerful identity which constructed by awareness of collective personality (?ahs-? manevi). The powerful identity, therefore, bases on the spirit of self-capability that will raise a progress and development. Referring to Said Nursi, this basic foundation of self-capability developed through three principles, namely self-interest versus self-sacrifice, extravagance versus frugality, and greed versus contentment. Then, by practicing and applying these three values, the prosperity and development can be achieved.